A Rare Case of Acute Cerebral Embolism from Left Atrial Myxoma Complicated by Postoperative Atrial Fibrillation - Khalid, Yaser; Dasu, Neethi; Dasu, Kirti; Daneshvar, Maziyar; Sailam, Vivek (Cardiology and Cardiovascular Medicine, 2020)
Primary cardiac tumors are those that originate in the heart and are extremely rare. Myxomas are the most common form of primary cardiac tumors. They have a variety of presentations, such as constitutional symptoms, cardioembolic events like cerebrovascular accidents (CVA), or hemodynamic abnormalities. Paroxysmal atrial fibrillation (PAF) is a well-known postoperative complication of coronary artery bypass grafting (CABG), but there are extremely few cases of PAF occurring post-operatively after left atrial myxoma surgical resection. We present a case of a 69- year-old female with a history of subarachnoid hemorrhage (SAH) who was diagnosed with CVA secondary to thromboembolism from left atrial myxoma. She then developed atrial fibrillation which required cardioversion. This case presents a challenge in terms of keeping left atrial myxoma as part of the differential diagnosis for cardioembolic CVA; deciding optimal timing for surgical resection; and finally, how to manage the subsequent new-onset atrial fibrillation.